Influences on Stakeholder Participation in Water Negotiations: A Case Study from the Klamath Basin. Issue 12 (1st December 2016) - Horangic, Alexandra; Berry, Kate A.; Wall, Tamara
ABSTRACT: In water governance, where problems are controversial and value laden, different forms of stakeholder involvement have become common and are frequently required. Stakeholder participation is often recognized as fundamental to the legitimacy and success of negotiated environmental decisions, but the intricacies of why stakeholders participate has received less attention. We examine factors that influenced stakeholder participation in the Klamath Basin Restoration Agreement and Klamath Hydroelectric Settlement Agreement of 2010. The research draws on in-depth, semistructured interviews of a sample recruited from stakeholder organizations in the Klamath River Basin. Results indicate that previous negative experiences did not translate into nonparticipation; divisions within seemingly aligned stakeholder organizations encouraged some stakeholders to participate and others to actively oppose negotiations; stakeholders' perceptions of power differentials encouraged both stakeholder participation and exclusion in negotiations; and concerns about relationship development during negotiations suggest that relationship building may be viewed as part of the negotiation process.